Fibrinolytic capacity increases with age in healthy humans, while endothelium-dependent vasodilation is unaffected - Gudnason, Thorarinn; Hrafnkelsdóttir, Thórdís; Wall, Ulrika; Swedberg, Karl; Jern, Sverker (Thrombosis and Haemostasis, 2003)
The capacity for stimulated endothelial release of tissue-type plasminogen activator (tPA) and endothelium-dependent vasodilation is diminished in patients with cardiovascular risk factors. We examined the effect of age on desmopressin-stimulated tPA release and endothelium-dependent vasodilation, using the perfused-forearm model. Thirty-two healthy subjects were divided into quartiles by age (mean age 24, 36, 54, and 72 years, respectively). Baseline fibrinolytic parameters, baseline forearm blood flow (FBF), and increase in stimulated FBF were all similar across age. By contrast, the capacity for desmopressin-stimulated release of tPA increased linearly by age. For tPA antigen, the total amount released (area-under-the-curve) was 1015, 1282, 2139, and 2845 ng/L tissue (p = 0.011) and the peak release rates were 62, 80, 113, and 163 ng/min/L tissue (p = 0.008) in the age-quartiles, respectively. A similar significant age-related response was observed for tPA activity. We conclude that in healthy individuals there is an up-regulation of the fibrinolytic response by age.
Keywords: Fibrinolysis; tissue-type plasminogen activator; endothelium; human; ageing